Integration of lean manufacturing and ergonomics in a metallurgical industry - Brito, Marlene (2018)
Striving to improve productivity, industries have used different management approaches, being lean manufacturing the most used over recent years. Lean manufacturing is based on value creation for the customer and elimination of waste that occurs during the production process, while improving working conditions. The incorporation of ergonomic aspects in the workstation design also contributes for the referred objectives, since it will reduce awkward postures or excessive effort during work, leading to better working conditions and increased productivity. The present study highlights, through a case study in four production areas of a metallurgical industry, the benefits of using an integrated operations management approach to improve productivity and ergonomic aspects. Several ergonomic methods, such as Rapid Upper Limb Assessment (RULA), Strain Index (SI), and Rapid Entire Body Assessment (REBA), were chosen to evaluate the ergonomic situation and lean manufacturing tools such as Value Stream Mapping (VSM) and 7 wastes were also used to analyze the systems and increase the productivity by eliminating several wastes. The results of this study show that it is possible, and desirable, to consider both aspects, ergonomic conditions and productivity, during continuous improvement’ implementations. In fact, the improvements reached through the advances in ergonomic conditions can contribute very positively for productivity increasing.